UPAYA KESIAPSIAGAAN BENCANA DI PERPUSTAKAAN MUSEUM KONFERENSI ASIA AFRIKA - Mentari Meilani; Oom Nurrohmah; Farah Ruqayah (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2022)
This study aims to determine the library's efforts to save collections when facing a disaster, especially disasters caused by human activities. Disasters in the form of human activities that can harm the library, such as theft, lack of security in institutions, fires and so on. The method used in this research is descriptive research method with a qualitative approach. Data collection techniques by means of observation, interviews and documentation studies. Informants in this study amounted to two people. The results of the study show that the Museum Library of the Asian-African Conference has chosen disaster preparedness efforts which are seen from four stages, namely, the prevention stage, the response stage, the reaction stage, and the recovery stage. The prevention stage is by carrying out an inspection of the library environment by the librarian and installing CCTV cameras. The response phase is by providing librarian disaster preparedness training and collaborating with the National Library of Indonesia in library collection preservation activities. The reaction stage, using evacuation route signs, APAR (Light Fire Extinguisher), and deposit boxes in the event of a disaster. The recovery phase is by collecting damage data and asking the National Library of Indonesia for help.Keywords: disaster preparedness, collection rescue, Asian African Conference Museum LibraryABSTRAKPenelitian ini bertujuan untuk mengetahui upaya perpustakan dalam menyelamatkan koleksi ketika menghadapi suatu bencana, terutama bencana yang disebabkan oleh ulah manusia. Bencana berupa ulah manusia yang dapat membahayakan di perpustakaan ini seperti pencurian, kurangnya pengamanan yang ada dalam institusi, kebakaran dan lain sebagainya. Metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dengan cara observasi, wawancara serta studi dokumentasi. Informan dalam penelitian ini berjumlah dua orang. Hasil penelitian menunjukkan bahwa Perpustakaan Museum Konferensi Asia Afrika sudah memilihi upaya kesiapsiagaan bencana yang dilihat dari empat tahap yaitu, tahap pencegahan, tahap tanggapan, tahap reaksi, dan tahap pemulihan. Tahap pencegahan dengan melakukan pemeriksaan lingkungan perpustakaan oleh pustakawan serta memasang kamera CCTV. Tahap tanggapan yaitu dengan memberi pelatihan kesiapsiagaan bencana pustakawan dan menjalin kerjasama dengan Perpustakaan Nasional Republik Indonesia dalam kegiatan preservasi koleksi perpustakaan. Tahap reaksi, dengan menggunakan rambu-rambu jalur evakuasi, APAR (Alat Pemadam Api Ringan), dan deposit box apabila terjadi bencana. Tahap pemulihan dengan melakukan pendataan kerusakan, dan meminta bantuan Perpustakaan Nasional Republik Indonesia.